2017
DOI: 10.5230/jgc.2017.17.e41
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Significance of Large Tumor Suppressor (LATS) Expression in Gastric Cancer

Abstract: PurposeThe aims of this study were to evaluate the expression of the large tumor suppressor (LATS) genes LATS1 and LATS2 by immunohistochemical staining of gastric cancer, and to evaluate the clinicopathological significance of LATS expression and its correlation with overall survival (OS).Materials and MethodsLATS1 and LATS2 expression in a tissue microarray was detected by immunohistochemistry, using 264 gastric cancer specimens surgically resected between July 2006 and December 2009.ResultsLow expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Once the Hippo signaling pathway is activated, MST1 and MST2 induce LATS1/2 phosphorylation; then, LATS1/2 kinases promote the binding of YAP1 to 14-3-3 proteins by phosphorylation, resulting in YAP1 inactivation and entrapment in the cytoplasm [48,49]. Numerous studies have shown that the tumor suppressor LATS2 is downregulated in various carcinomas and that this protein impedes tumor proliferation and invasion, e.g., in GC [20], nonsmall cell lung cancer (NSCLC) [50,51] and ovarian tumors [52]. Our previous studies assessed YAP1, a downstream transcriptional co-activator, which is overexpressed in gastric carcinoma and closely correlated with progression, metastasis and poor patient prognosis [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the Hippo signaling pathway is activated, MST1 and MST2 induce LATS1/2 phosphorylation; then, LATS1/2 kinases promote the binding of YAP1 to 14-3-3 proteins by phosphorylation, resulting in YAP1 inactivation and entrapment in the cytoplasm [48,49]. Numerous studies have shown that the tumor suppressor LATS2 is downregulated in various carcinomas and that this protein impedes tumor proliferation and invasion, e.g., in GC [20], nonsmall cell lung cancer (NSCLC) [50,51] and ovarian tumors [52]. Our previous studies assessed YAP1, a downstream transcriptional co-activator, which is overexpressed in gastric carcinoma and closely correlated with progression, metastasis and poor patient prognosis [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that antisense transcripts, especially non-coding RNAs, might regulate sense genes [19]. LATS2 expression is considered a good prognostic factor in GC [20]. Nevertheless, to the best of our knowledge, the expression and effects of LATS2-AS1-001 in human tumors have not been investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…They have been reported to govern cellular homeostasis by preventing cell proliferation and migration, by inducing cell death and senescence, and by regulating cell cycle checkpoints to maintain genetic stability (Visser and Yang 2010; Furth and Aylon 2017). Consistent with their proposed tumor-suppressive function, LATS proteins have been reported to be down-regulated in various cell types including breast cancer (Morinaga et al 2000), non-small lung cancer (Lin et al 2014), and gastric cancer (Son et al 2017). However, LATS was reported to be overexpressed in nasopharyngeal cancer (Zhang et al 2010), suggesting that the function of LATS remains controversial and may be tissue- and cancer-type dependent.…”
Section: Introductionmentioning
confidence: 83%
“…Clinically, LATS expression can have prognostic value. LATS1 and LATS2 expressions have been reported as significant markers for good prognosis in patients with gastric cancer (Son et al 2017), reduced LATS1 correlated with poor outcome with breast cancer patients (Takahashi et al 2005), and reduced LATS2 correlated with poor survival in acute lymphoblastic leukemia (Jiménez-Velasco et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Large tumor suppressor kinases 1/2 (LATS1/2) are core members of the Hippo pathway, and their activation is the major functional output of this pathway. LATS1 and LATS2 have the same function and are both expressed in GC ( 9 , 10 ). Although LATS1/2 are traditionally believed to inhibit tumor growth ( 11 , 12 ), Pan et al found that LATS1/2 deletion inhibits the growth of murine MC38 colon cancer cells ( 13 ).…”
Section: Introductionmentioning
confidence: 99%